Costly Collateral and the Public Supply of Liquidity - Schellekens, Philip (IMF Working Papers; Working Paper, 2000)
This paper addresses two complications arising from the use of collateral requirements in debt contracts between wealth-constrained entrepreneurs and banks. First, costly asset liquidation is found to enhance the susceptibility of debt finance to interest rate volatility. Second, aggregate uncertainty in conjunction with limited bank capitalization is shown to produce excessive credit constraints that, under certain conditions, justify the public supply of liquidity. The paper suggests applications with respect to models of interest rate smoothing and self-fulfilling currency crises.